How Does Politeness Emerge in Preoperational Stage - Liya Umaroh; Neni Kurniawati (ETERNAL (English Teaching Journal), 2019)
Preoperational stage starts from the age of two years to seven years. Through this year children be able to be behave politely. During this stage, children have started trying to distinguish what is good and bad things. In the concrete preoperational phase the child has begun to understand some rules that applies at home or school. The level of politeness has also been better applied. There are several politeness principle that can be used as a guidance in running a social life. The widely used maxim is the maxim of generosity, the children already understand about the meaning of sharing because since childhood their parents taught about the meaning of sharing which then they practice directly in school. Approbation maxim and tact maxim are seldom used by children because they have not yet been able to apply both maxim in a socializing